2014
DOI: 10.1371/journal.pone.0094550
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Lung Injury Induced by Common Bile Duct Ligation in Mice

Abstract: BackgroundLiver dysfunction and cirrhosis affect vasculature in several organ systems and cause impairment of organ functions, thereby increasing morbidity and mortality. Establishment of a mouse model of hepatopulmonary syndrome (HPS) would provide greater insights into the genetic basis of the disease. Our objectives were to establish a mouse model of lung injury after common bile duct ligation (CBDL) and to investigate pulmonary pathogenesis for application in future therapeutic approaches.MethodsEight-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(66 reference statements)
3
18
0
Order By: Relevance
“…CBDL mice develop intrapulmonary shunting and become hypoxemic on a background of cholestatic liver disease, which fulfills the three diagnostic criteria of HPS . To our knowledge, only one study has reported on CBDL in mice as a potential model for HPS, which, however, failed to demonstrate intrapulmonary shunts due to methodological issues . Our findings are in line with knowledge from human patients and prior work in rats, in which it was shown that shunts start to develop early after CBDL induction and do not require advanced fibrosis.…”
Section: Discussionsupporting
confidence: 89%
“…CBDL mice develop intrapulmonary shunting and become hypoxemic on a background of cholestatic liver disease, which fulfills the three diagnostic criteria of HPS . To our knowledge, only one study has reported on CBDL in mice as a potential model for HPS, which, however, failed to demonstrate intrapulmonary shunts due to methodological issues . Our findings are in line with knowledge from human patients and prior work in rats, in which it was shown that shunts start to develop early after CBDL induction and do not require advanced fibrosis.…”
Section: Discussionsupporting
confidence: 89%
“…For all experiments, PASMCs treated with normal rat serum or HPS rat serum come from the same split cells. The purity and identity of PASMCs was verified by their typical morphological pattern (peak and valley formation) and immunocytochemical staining with an antibody against SM-a-actin, as previously reported [23,24]. When the cells reached approximately 80% confluence, the original serum was replaced with 0.1% FBS.…”
Section: Cell Culturementioning
confidence: 90%
“…PubMed was searched for all messenger RNA (mRNA) microarray studies describing significantly upregulated gene expression in nonfetal lung cells or tissue in the setting of ALI, acute respiratory distress syndrome, pulmonary ischemia‐reperfusion, and/or primary pulmonary graft dysfunction. A total of 31 gene lists including 843 unique genes were identified from 23 articles . Based on the experimental models used in each study, these gene lists were subdivided into one of 3 “mechanical/noninfectious” categories (ischemia‐reperfusion, stretch, primary graft dysfunction) or one of 3 “toxic/infectious” categories (infection, sepsis, toxicity).…”
Section: Methodsmentioning
confidence: 99%
“…Genome‐wide microarray studies have previously demonstrated that ALI induces coordinated changes in the expression of hundreds of genes . We hypothesized that analyzing a representative subset of these previously described ALI‐related transcripts would allow for more precise, objective, and mechanistic evaluation of lung tissue injury and repair before, during, and after EVLP.…”
Section: Introductionmentioning
confidence: 99%